Hubungan Durasi Penggunaan Gadget Dengan Interaksi Sosial Pada Remaja Kelas X Di SMK Diponegoro Tumpang - Anita Mardiana; Risna Yekti Mumpuni; Kurnia Laksana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
In today's digital era, gadgets have become an integral part of everyday life, especially among teenagers. Excessive use of gadgets can affect adolescents' social interactions, which are an important phase in their psychosocial development. This causes changes in the way teenagers interact. This study aims to analyze the relationship between the duration of gadget use and social interaction in grade X adolescents at SMK Diponegoro Tumpang. The method used is correlational with a quantitative approach using a cross-sectional design. The sample in this study was 58 students with a Purposive Sampling sampling technique. The independent variable in this study is the duration of gadget use and the dependent variable is social interaction which is measured using a questionnaire on the level of gadget use duration and social interaction. The data analysis used is the Spearman Rank Test, the results show a value of p = 0.000 where p (˂0.05) and the correlation coefficient value (r = -0.439) this indicates that there is a relationship between the duration of gadget use and social interaction in adolescents. And there is a moderate negative relationship between the duration of gadget use and social interaction, which means that the longer the duration of gadget use, the lower the social interaction in adolescents. With the increasing use of gadgets among teenagers which often has a negative impact on social interaction relationships, it is hoped that this study can provide useful information for parents, educators, and teenagers themselves to manage gadget use more wisely.